PENGARUH PEMBELAJARAN KEWIRAUSAHAAN DAN KARAKTERISTIK WIRAUSAHA DALAM MENINGKATKAN MINAT BERWIRAUSAHA SISWA SMK - Jodhy, Sendhy Kurniawan; Wahyuni, Sri; Nugroho, Jonet Ariyanto (Department of Economics Education, Universitas Sebelas Maret, 2016)
The objectives of this research to test the influences (1) entrepreneurship-learning toward atittude toward entrepreneurship (2) entrepreneurship-learning toward subjective norm (3) entrepreneurship-learning toward perceived behavioral control (4) entrepreneur-characteristics toward atittude toward entrepreneurship (5) entrepreneur-characteristics toward subjective norm (6) entrepreneur-characteristics toward perceived behavioral control (7) subjective norm toward entrepreneurial interest (8) attitude toward entrepreneurship toward entrepreneurial interest (9) perceived behavioral control toward entrepreneurial interest.This research used quantitative descriptive method. The population of this research wereall XI-grade students in SMK Negeri 1 Sukoharjo which amounts to 356 students. The sample were selected 78 students through proportional random sampling. Data were collected by means of questionnaire. This research were used Structural Equation Modelling (SEM).The results showed that: (1) There were a negative and not significant influence between entrepreneurship-learning and attitude toward entrepreneurship (2) There were a positive and not significant influence between entrepreneurship-learning and subjective norm (3) There were a positive and not significant influence between entrepreneurship-learning and perceived behavioral control (4) There were a positive and significant influence between entrepreneur-characteristics and attitude toward entrepreneurship (5) There were a positive and significant influence between entrepreneur-characteristics and subjective norm (6) There were a positive and significant influence between entrepreneur-characteristics and perceived behavioral control (7) There were a positive and significant influence between attitude toward entrepreneurship and entrepreneurial interest (8) There were a positive and significant influence between subjective norm and entrepreneurial interest (9) There were a positive and significant influence between perceived behavioral control and entrepreneurial interest.